Sustainable packaging in footwear industry: Case study of PUMA - Lucie Sara Zavodna; Lucie Trejtnarova (Economics, Management and Sustainability)
Purpose. Modern companies are more focused on the life cycle of their products, so it comes also with sustainable packaging of products. Some companies do this on their own initiative, others because of customer's pressure. There are already several experiments, where companies introduced packaging that can be disposed of in an environmentally friendly way or reused. The main goal of the paper is to describe case study of sustainable packaging in the footwear industry. Main findings and implications. Even big producers of shoes are facing troubles with sustainable packaging solutions. The case study shows why PUMA abandoned the new sustainable packaging of shoes. After trying sustainable packaging, PUMA returned to the classic cardboard box in 2015.